2018
DOI: 10.3348/jksr.2018.78.6.380
|View full text |Cite
|
Sign up to set email alerts
|

The Safety of Protected Carotid Artery Stenting in Patients with Unstable Plaque on Carotid High-Resolution MR Imaging

Abstract: Purpose:The aim of this study was to determine the safety of the carotid artery stenting (CAS) procedure, using an embolic protection device which is based on the presence of unstable plaques on carotid MR imaging in patients who presented with severe carotid artery stenosis. Materials and Methods: This prospective study assessed 102 consecutive patients who had been noted with severe carotid stenosis. These patients underwent a preprocedural carotid MR imaging, and a periprocedural diffusion-weighted imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…It could predict recurrent ipsilateral stroke. 6,15,16 In our study, we analyzed imaging data considering all 3 characteristics of unstable plaques on carotid VWI and found that the percentage of patients with IPH was significantly higher than that of patients without IPH in the symptomatic group. This finding suggests that the measurement of luminal stenosis alone might not be sufficient for the source of stroke.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…It could predict recurrent ipsilateral stroke. 6,15,16 In our study, we analyzed imaging data considering all 3 characteristics of unstable plaques on carotid VWI and found that the percentage of patients with IPH was significantly higher than that of patients without IPH in the symptomatic group. This finding suggests that the measurement of luminal stenosis alone might not be sufficient for the source of stroke.…”
Section: Discussionmentioning
confidence: 86%
“…IPH is also strongly associated with recurrent ischemic events. It could predict recurrent ipsilateral stroke [ 6 , 15 , 16 ]. In our study, we analyzed imaging data considering all 3 characteristics of unstable plaques on carotid VWI and found that the percentage of patients with IPH was significantly higher than that of patients without IPH in the symptomatic group.…”
Section: Discussionmentioning
confidence: 99%